Spirit of challenge and its relationship to orientation towards competition in Iraqi weightlifters with physical disabilities - Abis Mohammed, Karim; Salman Abdul, Haider Ali (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study was to identify the spirit of challenge and the orientation towards competition among Iraqi weightlifters with physical disabilities. The researchers employed a descriptive approach. The research sample was composed of 19 weightlifters representing Baghdad clubs in the sport of weightlifting for individuals with physical disabilities. The tests utilized in the research included the Scale of the Spirit of Challenge and Orientation Towards Competition, as well as the Test of Raising Pressure from Lying on the Bench for Weightlifting for Individuals with Disabilities. Lifters with physical disabilities have a high level of challenge spirit. There is a significant correlation between the challenge spirit and the results of the competitions. Attention to psychological variables is crucial due to its significant impact on the outcomes of competitions in weightlifting for individuals with physical disabilities.